2019
DOI: 10.3389/fpls.2018.01939
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Adaptive Strategies of Oil Seed Crop Ricinus communis Early Seedlings (Cotyledon vs. True Leaf) Under Salt and Alkali Stresses: From the Growth, Photosynthesis and Chlorophyll Fluorescence

Abstract: Ricinus communis is an important energy crop and is considered as one of the most potential plants for salt-alkali soil improvement in Northeast China. Early seedling stage (such as the cotyledon expansion stage) is always a vulnerable stage but plays a vital role in plant establishment, especially under stress conditions. However, little information exists concerning the function of cotyledon and the relationship between cotyledon and true leaf in the adaptation to salt stress and alkali stress of this specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 47 publications
3
20
1
Order By: Relevance
“…Seedling establishment is one of the most sensitive and important stages of plant development in alkali-degraded soil [40]. In the present study, the dry weight of P. tenuiflora seedlings with or without AM decreased.…”
Section: Arbuscular Mycorrhizal Fungi Colonization and Seedling Growthsupporting
confidence: 43%
“…Seedling establishment is one of the most sensitive and important stages of plant development in alkali-degraded soil [40]. In the present study, the dry weight of P. tenuiflora seedlings with or without AM decreased.…”
Section: Arbuscular Mycorrhizal Fungi Colonization and Seedling Growthsupporting
confidence: 43%
“…A previous study reported that an increase in NPQ is thought to be an energy dissipation mechanism that protects the photosynthetic apparatus against excess light under salt stress [31]. Many studies reported an observed increase in NPQ in AMF-inoculated plants under salt stress [12,14]. These results indicate that AMF inoculation could improve the energy dissipation ability of a plant, which protects the photosynthetic apparatus against excess light under salt stress [15,32].…”
Section: Total Effectsmentioning
confidence: 86%
“…Chlorophyll fluorescence is a rapid, non-destructive method to determine changes in photosystem II and is used in many fields [29]. The Fv/Fm value can reflect the photo-inhibition level of PS II by estimating the maximum quantum yield of primary acceptor (QA) reduction [12]. A positive total impact on the Fv/Fm values of host plants under salt stress was confirmed in the present study, showing that AMF inoculation could alleviate photo-damage to PS II caused by stress [13].…”
Section: Total Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, "hangover effects" of deterioration may be carried through to later growth stages of the plant. Seedlings of deteriorated seeds may display reduced photosynthesis and transpiration [10,11], slower growth and ultimately lower yields [12]. Thus, even if poor quality seeds germinate or emerge, the quality of plants generated from such seed is not guaranteed [7,10,11].…”
Section: Introductionmentioning
confidence: 99%